Upaya Pemenuhan Kebutuhan Pengetahuan Tentang Nutrisi pada Ibu Menyusui - Fadhilatul Khoiriyah, Umi, Dr. Faizah Betty Rahayuningsih A., S.Kep, M.Kes (2017)
Background: Knowledge is one of a factor that affect on breastfeeding (ASI). However, a person who has knowledge should be supported by consciousness in behaving, because knowledge alone is not resulting a good behavior or positive behavior (Rahmawati, 2010). The nutrition is substances required by body to perform metabolism. In childbed women's nutritional needs especially that breast increase 25% because used for healing process of the body after giving birth and to produce breast milk (Wulandari & Handayani, 2011). Because of given health education intervention with the intention of increase knowledge and consciousness patient about the important of nutrition in breastfeeding mothers. Method: the author uses descriptive method, as sample is Ny. S, data were obtained by interview, observation, physical examination, and study documentation of journal and books. The result of research: after nursing care for three days, diagnosis emerging from Ny. S is a deficiency of knowledge related to lack of information about nutrition for breastfeeding mothers. Intervention: the action taken by author is observation of a knowledge patient level about nutrition, preached breast care, give to health education about variety nutrients needed breastfeeding mothers, terms of balance nutrition breastfeeding mothers, the nutrition needs of the breastfeeding mothers, something must be limited and impact of malnutrition breastfeeding mothers, and then give to support in compliance with nutrition to patient.